Mercury mobility in epibenthic waters of a deltaic environment - Cossa, Daniel; Dang, Duc Huy; Thomas, Bastien (PANGAEA, 2024)
Mercury (Hg) cycling at the sediment-water interfaces (SWI) encompasses a tangle of multiple homogeneous and heterogenous biogeochemical reactions whose resultant is not yet elucidated. Estuarine SWIs, where the organic matter mineralization is active, constitute experimental sites particularly suitable for scrutinizing Hg speciation and mobilization. Here, we present high-resolution vertical concentration profiles of Hg species, including inorganic divalent Hg (HgIIinorg) and monomethyl Hg (MMHg) in solid and dissolved (<0.22 µm) phases, on both sides of the SWI of the proximal part of the Rhône prodelta (northwestern Mediterranean Sea) using sediment cores and dialyzers implemented for a 67-day-long period. With Fe, Mn, Ca, P, and SO4 concentration profiles we identified the prevailing redox conditions: oxic in the epibenthic zone, anaerobic in the sediments starting at ~1 cm below the SWI, and sulfate-reducing zone below 13 cm. Although the site was under dynamic sedimentary conditions during the first days of the dialyzer's exposition, quasi-steady state conditions prevailed during the last 50 days of the experiment. Concentrations of the dissolved HgIIinorg species were <0.10 nM in the sediment pore waters but reached up to 0.58 nM in the epibenthic water zone, a concentration level that is ~200 times higher than that of the water column. Conversely, MMHg concentrations were low (<0.5 pM) above the SWI and increased to up to 4.6 pM in the sulfate and ferri-reducing zones of the sediment. The dynamic of the Hg species interconversions was explored using one-dimensional transport-reaction equations. This model allowed us to constrain the depth intervals where various species are produced or consumed and to approximate the reaction rates. We conclude that the epibenthic zone of the Rhône prodelta is a location of intense mobilization of inorganic HgII associated with organic matter mineralization and MMHg distribution in pore water is controlled by microbiological in-situ reactions, but sedimentary MMHg does not diffuse in the overlying water column.